Acceptability and completeness of vaccination schedules recommended for transgender women and travestis in the city of São Paulo, Brazil: a cross-sectional study, 2019-2020 - Cristina Langkammer Martins; Katia Cristina Bassichetto; Maria A. S. M. Veras (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To assess adherence to and completeness of vaccination schedules against human papillomavirus (HPV) and hepatitis A and B among transgender women and travestis in São Paulo, capital city of São Paulo state. Methods This was a secondary data analysis of the multicenter TransOdara study. Data were collected from 403 transgender women and travestis aged 18 years or older, recruited through respondent-driven sampling between December 2019 and October 2020. Results High adherence to vaccines was observed (88.8%), but completeness of the analyzed vaccination schedules was low: 12% (95%CI 8.0; 17.3) for hepatitis A, 7.2% (95%CI 3.5; 12.8) for hepatitis B and 8.1% (95%CI 3.0; 16.6) for HPV, with no statistically significant differences between them. Conclusion Despite high adherence, the low completion of vaccination schedules highlighted the need for diversified strategies to improve vaccination coverage and reduce the prevalence of vaccine-preventable sexually transmitted infections in this population.